Jensen’s) Inequality for the frequent functions an application study) - Al Z'ubi, Oruba Ahmed Saleh (Journal of natural sciences, life and applied sciences, 2017)
The researcher carried out a thorough and a deliberate study on (Jensen’s) Inequality and its complements in the repeated linear relations, as well as he introduced a number of applications on the same, besides some improvements that have been introduced on some areas of the Inequality